Can Gene Expression Analysis in Zero-Time Biopsies Predict Kidney Transplant Rejection? - Vonbrunn, Eva; Angeloni, Miriam; Büttner-Herold, Maike; Müller-Deile, Janina; Heller, Katharina; Bleich, Erik; Söllner, Stefan; Amann, Kerstin; Ferrazzi, Fulvia; Daniel, Christoph (Frontiers in Medicine, 2022)
Zero-time biopsies are taken to determine the quality of the donor organ at the time of transplantation. Histological analyses alone have so far not been able to identify parameters that allow the prediction of subsequent rejection episodes or graft survival. This study investigated whether gene expression analyses of zero-time biopsies might support this prediction. Using a well-characterized cohort of 26 zero-time biopsies from renal transplant patients including 4 living (LD) and 22 deceased donor (DD) biopsies that later developed no rejection (Ctrl, n=7), delayed graft function (DGF, n=4), cellular (TCMR, n=8) or antibody-mediated rejection (ABMR, n=7), we analyzed gene expression profiles for different types of subsequent renal transplant complication. To this end, RNA was isolated from FFPE sections and gene expression profiles were quantified. Results were correlated with transplant data and B-cell and plasma cell infiltration was assessed by immunofluorescence microscopy. Both principal component analysis and clustering analysis of gene expression data revealed marked separation between living and deceased donors. Differential expression analysis identified 185 significant differentially expressed genes (adjusted p value < 0.05). The expression of 68% of these genes significantly correlated with cold ischemia time (CIT). Furthermore, immunoglobulins were differentially expressed in zero-time biopsies from transplants later developing rejection (TCMR+ABMR) compared to non-rejected (Ctrl+DGF) transplants. In addition, immunoglobulin expression did not correlate with CIT but was increased in transplants with previous acute renal failure (ARF). In conclusion, gene expression profiles in zero-time biopsies derived from living donors are markedly different from those of deceased donors. Pre-transplant acute renal failure increased immunoglobulin expression, which might be involved in triggering later rejection events. However, these findings must be confirmed in larger cohorts and the role of early immunoglobulin up-regulation in zero-biopsies needs further clarification.